PERAN PEMERINTAH DALAM PENGAWASAAN PERIZINAN PENGUSAHAAN DAN PENANGKARAN BURUNG WALET BERDASARKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 3 TAHUN 2007 TENTANG USAHA PENGELOLAAN DAN PENGUSAHAAN SARANG BURUNG WALET - Hutagalung, Ayu Reda; Artina, Dessy; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This research discusses the role of the government in supervising permits for swallow cultivation and breeding based Pekanbaru City regional Regulation No. 3/2007 concerning the Management and Management of Swallow's Nest. article 6 paragraph 1 states that every person or entity that manages and operates swiftlet nests must have permission from the Mayor. However, after being passed, the regional regulation could not yet be implemented as it should. The facts in the field show in the implementation of supervision, that the breeding of swallow's nests in the city of Pekanbaru does not run according to applicable regulations.The type of legal research used by the author is the type of sociological legal research. This research was conducted in Pekanbaru City. the population and sample are parties related to the problem under study, namely the Pekanbaru City Environment and Sanitation Office, the Pekanbaru City Agriculture and Fisheries and Fisheries Office, the Investment Office and the One Stop City Integrated Service Pekanbaru, Swallow business owner in Pekanbaru City.From the results of this study the authors conclude that the role of the government in conducting surveillance carried out by the Department of Agriculture and Fisheries of the City of Pekabaru ad the Office of Environment and Cleanliness of the City of Pekanbaru, has not been implemented in accordance with existing regulations and management. Judging from the many swallow entrepreneurs in Pekanbaru City who have not registered their business licenses at the Pekanbaru City Investment and One Stop Integrated Service Office. The obstacle in implementing Pekanbaru's regional regulations in overseeing the management of swallow's nest business is the lack of Human Resources (HR), there are no more entrepreneurs coming to apply for licensing and supervision is not running because there is no complaint from the public in Pekanbaru city for swallow's nest entrepreneurs.Keywords: Oversight-Government-Entrepreneur of Swallow’s Nest